Trends of chlamydia and gonorrhea infections by anatomic sites among men who have sex with men in south China: a surveillance analysis from 2018 to 2022 - Xu, Wenqian; Li, Haiyi; Zhao, Peizhen; Wang, Jinshen; Liang, Peng; Wang, Cheng (BMC public health, 2024)
Chlamydia and gonorrhea notifications are rapidly rising in men who have sex with men (MSM). Currently, there are limited data on the prevalence of chlamydia and gonorrhea across various anatomical sites. Our study aimed to explore the prevalence, association and changing trends of urethral and rectal chlamydia and gonorrhea among MSM in Guangdong Province, China. We analyzed data among MSM attending sexually transmitted infections (STI) clinics in the Guangdong governmental sentinel network between 2018 and 2022. Chi-square tests were used to compare the difference, Join-point regressions for analyzing changing trends, and multivariate logistic regressions for examining associated factors. We included 4856 men in the analysis. Rectal chlamydia significantly increased from 13.8% to 26.4% over the past 5 years (average annual percentage change [AAPC] 19.2%, 95%CI 1.0-40.6, p = 0.043). After adjusting for covariates, chlamydia infection positively associated with main venue used to seek sexual partners (aOR = 2.31, 95%CI 1.17-4.55), having regular sexual partners in the past 6 months (aOR = 3.32, 95%CI 1.95-5.64), receiving HIV counselling and testing services (aOR = 2.94, 95%CI 1.67-5.17), receiving peer education (aOR = 1.80, 95%CI 1.14-2.83), infection with syphilis (aOR = 2.02, 95%CI 1.02-4.01) and infection with gonorrhea (aOR 7.04, 95% CI 3.01-16.48). Gonorrhea infection positively associated with having regular sexual partners in the past 6 months (aOR = 3.48.95%CI 1.16-10.49), and infection with chlamydia (aOR 7.03, 95% CI 2.99-16.51). To conclude, our findings reveal a high prevalence of chlamydia infections among MSM, particularly in the rectal area. Comprehensive chlamydia and gonorrhea health services are necessary for MSM to improve sexual health.